2016
DOI: 10.1021/acs.jpclett.6b02139
|View full text |Cite
|
Sign up to set email alerts
|

Transition from SAMO to Rydberg State Ionization in C60 in Femtosecond Laser Fields

Abstract: The transition between two distinct ionization mechanisms in femtosecond laser fields at 785 nm is observed for C60 molecules. The transition occurs in the investigated intensity range from 3 to 20 TW/cm2 and is visualized in electron kinetic energy spectra below the one-photon energy (1.5 eV) obtained via velocity map imaging. Assignment of several observed broad spectral peaks to ionization from superatom molecular orbitals (SAMOs) and Rydberg states is based on time-dependent density functional theory simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 39 publications
1
20
1
Order By: Relevance
“…Evidence was also found for the existence of excited fullerene SAMO states in fs laser photoelectron spectroscopy experiments. [2][3][4][5] Theoretical studies have confirmed the unusual nature of these lowest-lying members of Rydberg series in fullerenes, showing a deviation in the binding energies extrapolated from higher-lying, more conventional Rydberg states due to the proximity to the molecular core and also having a significant component of the electron density inside the hollow cage. 6 SAMO states have also been predicted in theoretical calculations of fullerene anions.…”
Section: Introductionmentioning
confidence: 89%
“…Evidence was also found for the existence of excited fullerene SAMO states in fs laser photoelectron spectroscopy experiments. [2][3][4][5] Theoretical studies have confirmed the unusual nature of these lowest-lying members of Rydberg series in fullerenes, showing a deviation in the binding energies extrapolated from higher-lying, more conventional Rydberg states due to the proximity to the molecular core and also having a significant component of the electron density inside the hollow cage. 6 SAMO states have also been predicted in theoretical calculations of fullerene anions.…”
Section: Introductionmentioning
confidence: 89%
“…Since its discovery, the soccer ball shaped C 60 -the archetypical fullerene -remains the focus of most ongoing scientific studies aimed at unveiling its properties (see [3] for an in-depth review). The nonlinear, nonresonant interaction of C 60 with strong femtosecond lasers has been the object of numerous investigations [4][5][6][7][8][9][10][11][12][13]. These studies revealed that at photon energies comparable with the separation between the first electronic excited state and the ground state (∼1.6 eV [14]), an efficient transfer of laser energy into C 60 's internal degrees of freedom occurs via electronic and nuclear (vibrational) couplings.…”
mentioning
confidence: 99%
“…The laser photoionization mechanisms of fullerenes have been found to be wavelength and pulse duration-dependent [9,10,18]. For IR pulses (800 nm) of about 30 fs duration and intensities below 5 × 10 13 W/cm 2 , it was found that multiphoton processes dominate when ionizing C 60 , while tunneling, and/or over-the-barrier ionization and ionization due to induced electron re-collision [8] have a low probability to occur under these conditions.…”
Section: Introductionmentioning
confidence: 99%